Building and Sustaining National ICT/Education Agencies : Lessons from Costa Rica (Omar Dengo Foundation) - Jimenez Iglesias, Carla (World Bank, Washington, DC, 2017)
Since its creation over 25 years ago, the Omar Dengo Foundation (ODF) has played a critical role in developments related to use of educational technologies in schools in Costa Rica. The integration of technology in Costa Rican public schools took off in 1987 with the creation by the Ministry of Public Education of the National Program of Educational Informatics, which became the flagship program of the newly created Omar Dengo Foundation. This paper explores the development of ODF as a key partner institution to the Costa Rican Ministry of Public Education and how changes in key legislation went hand-in-hand with ODF's growth and impact. It explores key lessons learned for policymakers looking for insights on how an external ICT/education agency can work productively in collaboration with the Ministry of Public Education and other government agencies to serve as main implementation agency for a large scale, national ICT in education initiative.